2011
DOI: 10.1021/nn2036957
|View full text |Cite
|
Sign up to set email alerts
|

Single-Particle Studies of Band Alignment Effects on Electron Transfer Dynamics from Semiconductor Hetero-nanostructures to Single-Walled Carbon Nanotubes

Abstract: We utilize single-molecule spectroscopy combined with time-correlated single-photon counting to probe the electron transfer (ET) rates from various types of semiconductor hetero-nanocrystals, having either type-I or type-II band alignment, to single-walled carbon nanotubes. A significantly larger ET rate was observed for type-II ZnSe/CdS dot-in-rod nanostructures as compared to type-I spherical CdSe/ZnS core/shell quantum dots and to CdSe/CdS dot-in-rod structures. Furthermore, such rapid ET dynamics can compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…a) Scheme of the PEC device. b) Energy levels (at pH = 13) of TiO 2 , PbS QDs (3 nm in diameter), CdS, related characteristic redox potentials . The arrows indicate the electrons and holes transfer process.…”
Section: List Of Analyzed Samplesmentioning
confidence: 99%
“…a) Scheme of the PEC device. b) Energy levels (at pH = 13) of TiO 2 , PbS QDs (3 nm in diameter), CdS, related characteristic redox potentials . The arrows indicate the electrons and holes transfer process.…”
Section: List Of Analyzed Samplesmentioning
confidence: 99%
“…As another example, Yuan et al utilized single-molecule spectroscopy (SMS) combined with time-correlated singlephoton counting to compare the electron transfer (ET) rates amongst type-II ZnSe-CdS dot-in-rod nanostructures, type-I spherical CdSe-ZnS core-shell quantum dots, and CdSe-CdS dot-in-rod structures, respectively. 131 Their time-resolved fluorescence measurements on single nanocrystals of various types indicated that electron transfer to nearby CNTs is most effective for dot-in-rod heterostructures with a type II band alignment. Indeed, the electron transfer dynamics of ZnSe-CdS QD/nanorod nanostructures prevailed over both Auger and radiative recombination processes, thereby rendering these materials as promising candidates for photovoltaic applications.…”
Section: Carbon Nanotube (Cnt)-chalcogenide Semiconductor Heterostruc...mentioning
confidence: 99%
“…However, the reports of using ternary or quaternary semiconductors to manipulate the interfacial band alignment have been scarce, so far. 23,24 In this context, an interesting alternative to the tuning of the absorption region is the formation of alloy structures, allowing for the band gap variation by changing the composition of the QDs. Examples include alloyed Zn x Cd 1Àx Se QDs, the band gap of which can be varied by changing x between the values of the pure ZnSe and the pure CdSe QDs of the same size and crystal structure.…”
Section: Introductionmentioning
confidence: 99%